SURVEY ON BANK INTERNAL AUDIT FUNCTION - Kristo, Elsa (European Scientific Journal, ESJ, 2013)
The ongoing global crisis and the importance of the banking system stability as a dominant sector within Albanian financial system, makes the role of internal audit crucial. Despite the importance of this function, is internal audit at the required professional level to protect the banks from the complexity of risks they are exposed? Do the auditees believe that internal audit adds value to the banks and improves operations, thus helping the organization to meet its objectives? This paper will introduce the findings of a survey on the role of internal auditors in the Albanian banking system. The results of the study show the absolute necessity of the internal audit, however it has to be highlighted that there is still room for improvement of some specific competencies of internal audit.